1970
DOI: 10.1136/jnnp.33.4.544
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic function in amyotrophic lateral sclerosis

Abstract: SUMMARY No abnormality of exocrine function of the pancreas was found in 10 patients with amyotrophic lateral sclerosis. Eight patients showed abnormal glucose metabolism, attributed to the effects of age, malnutrition, diminished physical activity, and decreased muscle mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This histocompatability antigen is also increased in Japanese patients with Hashimoto's thyroiditis." 5 The presence and significance of circulating immune complexes in the serum of patients with motor neurone disease has recently been noted and discussed by Oldstone et al 6 Their studies have so far failed to reveal any specific viral or myelin antigens in tissues subject to deposition of these immune complexes. The production of antibodies and the formation of immune complexes may be a secondary response to damaged neural tissue rather than a primary response to a causative agent such as a virus or a central nervous system specific protein.…”
Section: Discussionmentioning
confidence: 99%
“…This histocompatability antigen is also increased in Japanese patients with Hashimoto's thyroiditis." 5 The presence and significance of circulating immune complexes in the serum of patients with motor neurone disease has recently been noted and discussed by Oldstone et al 6 Their studies have so far failed to reveal any specific viral or myelin antigens in tissues subject to deposition of these immune complexes. The production of antibodies and the formation of immune complexes may be a secondary response to damaged neural tissue rather than a primary response to a causative agent such as a virus or a central nervous system specific protein.…”
Section: Discussionmentioning
confidence: 99%
“… Utterback et al. (1970) analyzed the pancreatic function of 10 ALS patients and 1 patient with chronic pancreatitis.…”
Section: Gastrointestinal (Gi) Disorders In Human Alsmentioning
confidence: 99%
“…This study raised the question if there is a direct relationship between ALS and the pancreas or if alterations of the pancreas are due to secondary complications. Utterback et al (1970) analyzed the pancreatic function of 10 ALS patients and 1 patient with chronic pancreatitis. They found that the patients experienced a variety of intestinal symptoms.…”
Section: Gastrointestinal (Gi) Disorders In Human Alsmentioning
confidence: 99%
“…Of these, nineteen reported impaired insulin secretion [48][49][50][51][52][53] or signaling. [54][55][56][57][58][59][60][61][62][63][64][65][66] Only two early papers reported normal glucose tolerance, one using neurological patients rather than healthy controls, 67 and one not using controls at all. 68 Another paper found increased plasma and CSF alpha-hydroxybutyrate (a pre-diabetes marker), 69 and another reported insulin resistance (IR) in bvFTD.…”
Section: Insulin Is Impaired In Alsmentioning
confidence: 99%